2021
DOI: 10.1155/2021/8484391
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Mechanical Characteristics of Impact Rock under the Combined Action of Different Constant Temperatures and Static and Dynamic Loads

Abstract: The complex mechanical environment of deep coal and rock masses leads to obvious changes on their dynamic mechanical properties. However, there are few reports on the dynamic mechanical properties of rocks under the combined action of medium temperature (normal temperature ∼100°C) and static and dynamic loads. In this paper, a dynamic load and temperature combined action Hopkinson pressure bar experimental system is used to experimentally study the impact type of a fine sandstone under temperature conditions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…In this experiment, the SHPB experimental system developed by the China University of Mining and Technology, which is composed of SHPB test system, ultra high-speed strain acquisition system, DIC image analysis system, and temperature control system [36]. The high-speed strain acquisition system consists of an ultra-dynamic strain gauge (LK2107 B, 16 bit, 8-channel), strain gauge junction boxes, and strain gauges, with a sampling rate of 40 MHz.…”
Section: Experimental Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…In this experiment, the SHPB experimental system developed by the China University of Mining and Technology, which is composed of SHPB test system, ultra high-speed strain acquisition system, DIC image analysis system, and temperature control system [36]. The high-speed strain acquisition system consists of an ultra-dynamic strain gauge (LK2107 B, 16 bit, 8-channel), strain gauge junction boxes, and strain gauges, with a sampling rate of 40 MHz.…”
Section: Experimental Systemmentioning
confidence: 99%
“…The preset bullet incidence velocity was 1.0 m/s, and the gas chamber pressure setting was 0.06 MPa. The density of fine sandstone was between 2.32 g/cm 3 and 2.42 g/cm 3 , and the bullet incidence velocity during the experiment was 1.00 to 1.31 m/s [36]. Figure 3 characterizes the variation of fine sandstone's dynamic stress and strain under seismic loading and different temperature conditions.…”
Section: Dynamic Mechanical Characteristics Of Fine Sandstone At Diff...mentioning
confidence: 99%
“…In the context of dynamic loading, the mechanical properties of thermally treated rocks, such as compressive strength and tensile strength, are also influenced by the rate at which they are subjected to strain or load. During the last five years, several researchers have made efforts to comprehend how rocks behave dynamically under high-temperature conditions 7 10 . An et al 7 explored the dynamic testing of marble to ascertain both its uniaxial compressive strength and Brazilian tensile strength under varying temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Their conclusions highlighted the increasing brittleness of sandstone up to 400 °C, followed by a slight transition toward ductility up to 800 °C. In a related context, Zhao et al 10 studied the dynamic compressive strength of sandstone under high-temperature conditions. Their research revealed that the peak strength of sandstone exhibited an increase up to 100 °C.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation